Exploring the microbiota of the red-brown defect in smear-ripened cheese by 454-pyrosequencing and its prevention using different cleaning systems. (April 2017) - Guzzon, Raffaele; Carafa, Ilaria; Tuohy, Kieran; Cervantes, Gonzalo; Vernetti, Luca; Barmaz, Andrea; Larcher, Roberto; Franciosi, Elena
Abstract: Red-brown pigmentation can occasionally form in smeared-ripened cheese such as Fontina during the ripening process. This reaction is due to over-development of the typical microbiota present on the rind. Previous studies have demonstrated the relationship between red-brown pigmentation and the traditional utilization of wooden shelves during cheese ripening. The first part of the paper focuses on the characterisation of yeast and bacterial microbiota: plate counts and 454-pyrosequencing were performed in spoiled (n = 6) and non-spoiled cheeses (n = 6) and on the wooden shelves used during ripening. The second part shows different systems tested for cleaning the wooden shelves and avoiding the development of the red-brown defect in cheese: washing with hot water and ozone treatment. Actinobacteria, dominated on the wooden shelves, suggesting to be responsible for the red-brown pigmentation; they were also found in traces in the defected cheese samples. Galactomyces and Debaryomyces were the main species characterizing the yeast population, with Debaryomyces being the most dominant species on the shelves used during ripening of the red-brown defective cheese. Hot water treatment reduced the microbial contamination of shelves, whereas only the ozone treatment ensured complete elimination of both yeast and bacteria, resulting in the cheese rind not having the red-brown defect. Highlights: The microbiota on shelves and in cheese was characterised using 454-pyrosequencing. Shelf microbiota had a role in the red-brown defect in cheese. Two cleaning treatments using water and ozone were tested on the wooden shelves. Ozone was more successful than water in reducing microbial counts on the wooden shelves.